Ảnh hưởng của các đặc điểm người dẫn dắt phiên phát trực tiếp và trò chơi hóa đối với ý định mua hàng ngẫu hứng - Nguyễn Thị Hoàng, Yến; Nguyễn Viết, Bằng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Drawing on the Stimulus-Organism-Response (S-O-R) framework and Self-Determination Theory (SDT), this study investigates how Streamer characteristics (professionalism, real-time interactivity, attractiveness, and image matching) and gamification influence consumers’ impulse buying intentions, through the organism role of enjoyment. Data were collected through an online survey of 357 consumers and analyzed using PLS-SEM. Practically, the findings highlight gamification as an independent strategic tool that livestream platforms and businesses can leverage to stimulate impulsive purchasing behavior. Theoretically, this study extends the application of the S-O-R framework in the livestream commerce context by clarifying the catalytic role of enjoyment as a central emotional mechanism linking Streamer characteristics to impulse buying intention.